Positioning of AfD in the Russian-Ukrainian war - Bernete-García, Francisco; Llama-Irastorza, Araceli (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Through a content analysis of texts published in the AfD Kompakt magazine, it is found that there has been no change in the political positions of the AfD (Alternative for Germany) party as a result of the war in Ukraine. This war provides the magazine AfD Kompakt with new arguments to disqualify the German coalition government and its foreign policy, without ceasing to refer to the economy or energy and without ceasing to mediate in the battle for how to get out of the crisis.